Analisis Perkuatan Rangka Atap Baja pada Bangunan Gedung Heritage 1921 Menggunakan Software SAP 2000 - Prima Arga Rumbyarso, Yonas (Publica Scientific Solution, 2022)
Introduction: The roof truss construction used in the cultural heritage building in this analysis is a truss roof truss with 2L angle steel profiles (double elbow) 40.40, 50.50, 60.60, 70.70, IWF steel profile gording 150x150, and roof tile coverings, with a length ofroof 102 m, width 21.6 m, height 5 m, with a distance of 7.4 m and 4.1 m truss. The cultural heritage building discussed in this analysis is the roof, namely the horses. Method: The method used in this study is to collect data in the form of shop drawings. The purpose of the study was to identify the capability of the roof structure with the updated loading regulations RSNI 1727-2018. Results: This analysis uses the latest RSNI 1727-2018 loading regulations and the latest SNI 1729-2015 steel regulations, does not change the installed materials and existing shapes, and does not use earthquake and rain loads, only live/maintenance loads, heavy dead loads. roof coverings, ceilings and hangers, and compressed and suction wind loads. Conclusion: From the resultsof this analysis, it is assumed that the rusted steel profile has been replaced, there are two truss rods that need to be replaced with a 2L 80.80 double angled profile with initial data of a 70.70 2L profile. Analysis of the 3-dimensional roof structure with SAP2000 software by reviewing the dead load, the live load of workers according to the loading regulations of the RSNI 1727-2018, taking into account the compressed wind load of 75.82 m2, the suction wind load of 57.37 m2 according to the wind speed of 40 m/s